Salmonella typhimurium Encodes a Putative Iron Transport System within the Centisome 63 Pathogenicity Island - Zhou, Daoguo (American Society for Microbiology, 1999)
Upon entry into the host, Salmonella enterica strains are presumed to encounter an iron-restricted environment. Consequently, these bacteria have evolved a variety of often-redundant high-affinity acquisition systems to obtain iron in this restricted environment. We have identified an iron transport system that is encoded within the centisome 63 pathogenicity island of Salmonella typhimurium. The nucleotide composition of this locus is significantly different from that of the rest of this pathogenicity island, suggesting a different ancestry and a mosaic structure for this region of the S. typhimurium chromosome. This locus, designated sit, consists of four open reading frames which encode polypeptides with extensive homology to the yfe ABC iron transport system of Yersinia pestis, as well as other ABC transporters. The sitA gene encodes a putative periplasmic binding protein, sitB encodes an ATP-binding protein, and sitC and sitD encode two putative permeases (integral membrane proteins). This operon is capable of complementing the growth defect of the enterobactin-deficient Escherichia coli strain SAB11 in iron-restricted minimal medium. Transcription of the sit operon is repressed under iron-rich growth conditions in a fur-dependent manner. Introduction of a sitBCD deletion into wild-type S. typhimurium resulted in no apparent growth defect in either nutrient-rich or minimal medium and no measurable virulence phenotype. These results further support the existence of redundant iron uptake systems in S. enterica.